A modest proposal : for preventing the children of poor people in Ireland, from being a burden to their parents or country ; and for making them beneficial to the publick /: for preventing the children of poor people in Ireland, from being a burden to their parents or country ; and for making them beneficial to the publick. (2015) - Swift, Jonathan, 1667-1745
No abstract available